Neurofeedback training for alcohol dependence versus treatment as usual: study protocol for a randomized controlled trial. Issue 1 (December 2016) - Cox, W.; Subramanian, Leena; Linden, David; Lührs, Michael; McNamara, Rachel; Playle, Rebecca; Hood, Kerenza; Watson, Gareth; Whittaker, Joseph; Sakhuja, Raman; Ihssen, Niklas
Abstract Background Real-time functional magnetic resonance imaging (rtfMRI) is used for neurofeedback training (NFT). Preliminary results suggest that it can help patients to control their symptoms. This study uses rtfMRI NFT for relapse prevention in alcohol dependence. Methods/design Participants are alcohol-dependent patients who have completed a detoxification programme within the past 6 months and have remained abstinent. Potential participants are screened for eligibility, and those who are eligible are randomly assigned to the treatment group (receiving rtfMRI NFT in addition to treatment as usual) or the control group (receiving only treatment as usual). Participants in both groups are administered baseline assessments to measure their alcohol consumption and severity of dependence and a variety of psychological and behavioural characteristics that are hypothesised to predict success with rtfMRI NFT. During the following 4 months, experimental participants are given six NFT sessions, and before and after each session various alcohol-related measures are taken. Participants in the control group are given the same measures to coincide with their timing in the experimental group. Eight and 12 months after the baseline assessment, both groups are followed up with a battery of measures. The primary research questions are whether NFT can be used to teach participants to down-regulate their brain activation in the presence of alcohol stimuli or to up-regulate their brain activation in response to pictures related to healthy goal pursuits, and, if so, whether this translates into reductions in alcohol consumption. The primary outcome measures will be those derived from the functional brain imaging data. We are interested inimprovements (i.e., reductions) in participants' alcohol consumption from pretreatment levels, as indicated by three continuous variables, not simply whether or not the person has remained abstinent. The indices of interest arepercentage of days abstinent, drinks per drinking day, andpercentage of days of heavy drinking . General linear models will be used to compare the NFT group and the control group on these measures. Discussion Relapse in alcohol dependence is a recurring problem, and the present evaluation of the role of rtfMRI in its treatment holds promise for identifying a way to prevent relapse. Trial registration ClinicalTrials.gov Identifier:NCT02486900, registered on 26 June 2015.